RAMADAN FASTING AMONG PAEDIATRIC PATIENTS WITH CONGENITAL ADRENAL HYPERPLASIA (CAH) - Guang, Gan Cheng; Lordudass, Alexis Anand Dass A/L; Peng, Cheng Hooi; Binti Mat Amin, Noor Arliena; Teik, Teoh Sze; Lyn Jeanne, Wong Sze; Selveindran, Nalini; Hua, Janet Hong Yeow (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION All postpubescent Muslims, with exceptions, are requested to fast during Ramadan. However, patients with illnesses often want to fast despite medical risks to their health. To our knowledge, there are no studies on fasting among children with CAH, and the risks of prolonged fasting are not known. We seek to explore their experiences during fasting. METHODOLOGY This is a cross-sectional study using a questionnaire over an estimated period of 6 months. All children with CAH being seen at Hospital Putrajaya who had attempted fasting during Ramadan or wished to fast in the future were included. RESULTS 18 females and 16 males with a mean age of 9.6 ± 0.982 years (3–17) were recruited. Twenty-seven patients (79.4%) tried to fast but only twelve (44%) sought the advice of a paediatrician. Nine (75%) fasted despite being advised against fasting. Complications which occurred in 13 patients (48.2%) included the following: asthenia (92.3%), thirst (30.7%), dehydration (23%), and hypoglycaemic symptoms (61%). None were hospitalised. Twelve patients (44%) were able to fast for the whole month. Non-fasters were significantly younger than fasters [adjusted OR (95%CI) = 1.9437 (1.09–3.43), p=0.02]. Fasters were less aware of the potential complications from fasting [adjusted OR (95%CI) = 0.07 (0.007–0.68), p=0.02]. The frequency of adequate knowledge on safe fasting practices during Ramadan was significantly lower in full-month-fasters vs. partial-month-fasters [adjusted OR (95%CI) = 0.079 (0.008–0.781), p=0.02]. Non-compliant-fasters were significantly more likely to experience complications vs. compliant-fasters during fasting [adjusted OR (95%CI) = 8.3 (1.47–47.22), p=0.01]. CONCLUSION A significant number of paediatric patients with CAH who observed Ramadan fasting without a paediatrician’s advice is a cause for concern. In paediatric CAH patients, fasting can cause complications especially if compliance with medications is an issue.